(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
An investigation of the interaction of 5CB and 6CB liquid crystals along with their dimer configurations in different conformations. The total energy, thermal energy, HOMO-LUMO Gap, dipole moment, polarizability, constant volume heat capacity, entropy, zero-point energy (ZPE), and enthalpy of the different configurations of 5CB and 6CB liquid crystal dimers are affected during the molecular interaction. The different interaction properties of 5CB, 6CB, and 5CB-6CB dimers studied in parallel and antiparallel conformation with the help of density functional theory method lc-blyp by NWChem software package. The 5CB and 6CB liquid crystal dimers have the least dipole moment and negative entropy in the antiparallel conformation. The cross conformation of 5CB liquid crystal dimer (5CB-5CB) has the least isotropic polarizability; however, the parallel conformation of 5CB liquid crystal dimer has the highest isotropic polarizability. The isotropic polarizability is minimum in the antiparallel conformation of 6CB liquid crystal dimer (6CB-6CB), while isotropic polarizability is maximum in the parallel conformation of 6CB liquid crystal dimer. The 5CB liquid crystal dimer and 6CB liquid crystal dimer have minimum negative interaction energy in the antiparallel conformation, but 5CB-6CB liquid crystal dimer has positive interaction energy for all the possible conformations.